itu ANALISIS HARGA KONSUMEN BERAS TAHUN 2021-2025 DI INDONESIA: Pendekatan Time Series - Syaharani, Deswita; MT Napitupulu, Dompak; Yanita , Mirawati; Hidayati , Rahmi (Universitas Jambi, 2026)
Rice is a strategic staple food in Indonesia, and fluctuations in its consumer price have significant implications for food security and household welfare. This study aims to: (1) examine the trend and seasonal fluctuations of rice consumer prices in Indonesia during 2021–2025, (2) analyze the factors influencing rice price movements, and (3) project rice consumer prices for the subsequent two years. The study employs monthly secondary time-series data from January 2021 to December 2025. Descriptive analysis is used to identify price trends and seasonal patterns, while multiple linear regression is applied to assess the effects of inflation, rice production, rice import volume, and the rupiah–US dollar exchange rate on consumer rice prices. Price projections are conducted using linear trend analysis. The results indicate that rice consumer prices in Indonesia exhibit an overall upward trend accompanied by noticeable seasonal fluctuations. Empirical findings show that inflation has a negative and statistically significant effect on rice prices, while rice import volume and the rupiah–US dollar exchange rate have positive and significant effects. In contrast, rice production does not significantly influence consumer rice prices during the study period. Price projections suggest that rice consumer prices are expected to continue increasing over the next two years. The novelty of this study lies in its integrated analysis of trend behavior, seasonal fluctuations, and price projections using recent post-pandemic monthly data (2021–2025), providing updated empirical evidence on rice price dynamics in Indonesia. The findings offer practical implications for policymakers, particularly in designing effective price stabilization strategies, managing rice imports, and maintaining exchange rate stability to safeguard consumer purchasing power and national food security.